FEATURES OF THE MUSLIM DRESS CODE OF URBAN YOUTH OF DAGHESTAN (ON THE EXAMPLE OF THE STUDENTS OF THE DAGHESTAN STATE UNIVERSITY) - Zul'pukarova, El'mira Magomed-Gereevna; Seferbekov, Ruslan Ibragimovic (History, Archeology and Ethnography of the Caucasus, 2018)
One of the elements of the material culture is clothing. The traditional clothing of the peoples of Daghestan, which has been similar to the national costumes of other peoples of the Caucasus, bears a special ideological and imaginative content and variety of functions reflecting their ethnic kinship, historical and cultural ties and mutual influences. Clothes, worn according to the precepts of Islam, can be considered one of the components of the traditional Daghestan costume. Clothing was an important component of the daily life of the residents of Daghestan. Significant changes in the clothing of the peoples of Daghestan occurred during the Soviet era. They were associated with the spread of factory products, formation of new needs and standards of life, which led to the disappearance of most types of national clothing. Further loss of elements of the traditional Daghestan national costume takes place during the years of the so-called «perestroika» and especially in the post-Soviet period under the influence of urbanization and globalization. At the same time, new types of clothing appear. Especially in the youth environment a special type of fashion was formed, which can be described as «regional Daghestan fashion». A special category of young people is made up of students who share common interests, group self-awareness, a specific subculture and lifestyle. One of the elements of this particular subculture is the student's costume. Based on the paper of the ethno-sociological survey of students of two faculties of the Daghestan State University conducted by the authors, the features of the Muslim dress code for the youth of the city of Makhachkala have been examined. The study of this category of youth leeds to the conclusion that in the cities of Daghestan in the post-Soviet period a special fashion has developed, oriented on the norms and prohibitions of Islam concerning the rules of wearing clothes. In all other respects, the costume of these students is not much different from that of their peers in other regions of Russia.
Keywords: material culture; clothing; Muslim dress code; regional fashion; youth of Daghestan